2019
DOI: 10.1158/1538-7445.sabcs18-p1-13-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P1-13-01: Final results of the ASG1-3 study, a randomized phase III study comparing a standard dose chemotherapy with epirubicin/cyclophosphamide and paclitaxel with a dose dense regimen with epirubicin and paclitaxel

Abstract: Background Dose dense chemotherapy (DDT) has shown improvements of disease-free survival (DFS) and overall survival for primary breast cancer patients with a high risk of relapse. There are much less data about the effect of DDT in patients with intermediate risk of recurrence (1-3 positive axillary lymph nodes). Aim of this prospectively randomized trial was to investigate the superiority of a DDT schedule over a standard chemotherapy (ST) in primary breast cancer patients with 1-3 positive axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several additional studies 77,78,[95][96][97][98] also showed a trend toward a positive relationship between the HER2 alteration and benefit from dose intense anthracyclines. Dhesy-Thind 90 performed a meta-analysis 78,92,96 , using FISH data from the Belgian study 78 and data from the high dose and medium dose anthracycline arms from the CALGB 8541 analysis 91 .…”
Section: Does the Her2 Alteration Affect Sensitivity To Anthracyclines?mentioning
confidence: 99%
“…Several additional studies 77,78,[95][96][97][98] also showed a trend toward a positive relationship between the HER2 alteration and benefit from dose intense anthracyclines. Dhesy-Thind 90 performed a meta-analysis 78,92,96 , using FISH data from the Belgian study 78 and data from the high dose and medium dose anthracycline arms from the CALGB 8541 analysis 91 .…”
Section: Does the Her2 Alteration Affect Sensitivity To Anthracyclines?mentioning
confidence: 99%